Development, characterisation and translocation of valproic acid-encapsulated nanoemulsion across blood-brain barrier - Tan, Suk Fei (2017)
Valproic acid (VPA) is a widely used antiepileptic drug (AED) for epilepsy especially in generalized and absence seizures. However, VPA has high plasma protein binding (90 % - 95 %) so only low amount of free VPA were able to reach the brain. An increase in therapeutic dose is not feasible as it will further aggravate the toxicity problem because VPA has a narrow therapeutic window range of 50-150 μg/mL in plasma. The presence of brain-to-blood efflux transporter in blood-brain barrier (BBB)further reduces the bioavailability of VPA in the brain. Taken together, the efficacy of VPA in treating epilepsy is hampered by high plasma protein binding nature, narrow therapeutic window and low brain bioavailability. The currently marketed parenteralVPA only enhances the solubility of the drug in water. Therefore in this study, a formulation of parenteral nanoemulsion of VPA was developed to reduce the clearance of VPA, to improve the tolerable concentration of VPA and the brain bioavailability of VPA. In our study, valproic acid-encapsulated nanoemulsions (VANE) were formulated by dispersing an oil phase containing VPA and lecithin into an aqueous phase containing tween 80 (T80). Among all types of oils studied, safflower seed oil was used as an oil phase in VANE as it formed the smallest droplet size of VANE. Alpha-tocopherol were also added into the oil phase to reduce the lipid peroxidation of oil phase in VANE. To further reduce the droplet size of VANE, the optimum processing conditions of ultrasonicator were studied (temperature, energy intensity and time) and used to further emulsify the VANE. Next, four VANEs with different percent composition (F1, F2, F3 and F4) were formulated to study the effect of oil phase content and drug-to-oil phase ratio on the physical properties of VANE (droplet size, polydispersity index (PDI) and zeta potential). Eventually, two nanoemulsions namely F3 VANE and F4 VANE out of these four formulations were selected to be studied in the following studies as they had higher drug content at desirable physical characteristic (droplet size <200 nm, PDI <0.2). Both VANEs had physiologically compatible pH (around 8), osmolarity and viscosity. Both VANEs were spherical in shape and encapsulated more than 97% of VPA. Stability studies showed that F3 VANE was more stable than F4 VANE as F3 VANE showed only little changes in droplet size and PDI at storage of high temperature (45 °C) over five months. The in vitro drug release also indicated F3 VANE had more and faster VPA release compared to F4 VANE. This was probably due to lower surfactant-to-oil ratio and higher percentage of oil in F3 VANE, exhibited less barrier for VPA release. F3 VANE (IC50: 633.19 μg/mL) also had less cytotoxic effect on hCMEC/D3 cells compared to F4 VANE (IC50: 402.69 μg/mL). Next, the in vitro BBB model was successfully developed with appropriate optimization and characterization. It was then used to assess the in vitro drug penetrability of F3 and F4 VANE where both VANEs penetrated the in vitro BBB as freely as VPA. Comparing both of the VANEs, F3 VANE was physically and biologically more attractive as it had higher drug content, better stability and less cytotoxic effect. Hence, only VPA and F3 VANE were studied in vivo studies. F3 VANE had improved the total bioavailability of VPA, reduced the clearance of VPA, and prolonged the half life of VPA in the blood from F3-treated rats compared to VPA-treated rats. The improvement of bioavailability of F3 VANE in the brain was also observed. This is possibly due to (a) higher bioavailability of F3 VANE in blood (b) lower clearance rate of F3 VANE in the brain by possible inhibition of T80 to P-gp. Overall, F3 VANE had successfully reduced the cytotoxicity of VPA, the clearance of VPA and prolonged the half-life of VPA in the blood, subsequently improved the brain bioavailability of VPA significantly.